Analisis tingkat kepuasan konsumen terhadap pelayanan kefarmasian di apotek pendidikan X Kabupaten Magelang - Bunga, Cut Dewi; Rianawati, Luluc; Yulaikah, Ariska; Latifah, Elmiawati; Yuliastuti, Fitriana; Pribadi, Prasojo (Borobudur Pharmacy Review, 2025)
The growing recognition of health's significance among the public drives healthcare facilities such as pharmacies, to enhance the quality of their services. Pharmacies are increasingly emphasizing pharmaceutical services that have transitioned from a drug-centric approach to one that prioritizes the patient. This shift aligns with the principle of pharmaceutical care, which focuses on enhancing the quality of life for patients, while also responding to the growing competition in the market and the demands for consumer satisfaction. Educational pharmacies serve a crucial function as a venue for learning and practical experience for future professionals in the pharmaceutical field. This investigation seeks to assess the degree of consumer satisfaction regarding pharmaceutical services at Pharmacy Education X located in Magelang Regency. The study employs a quantitative descriptive methodology utilizing Likert scale measurements. This study employs a cross-sectional design utilizing a questionnaire that encompasses five dimensions: empathy, physical aspects, responsiveness, assurance, and reliability, aimed at assessing consumer satisfaction. The sample included 100 respondents selected through the convenience sampling method. The findings for the empathy dimension were 96.8%, the physical dimension also recorded 96.8%, the responsiveness dimension showed 96.3%, the assurance dimension reached 98.3%, and the reliability dimension was at 97.5%. In summary, there is a high level of satisfaction among consumers regarding the pharmaceutical services provided at Educational Pharmacy X in Magelang Regency, reflected in an impressive average consumer satisfaction percentage of 97.14%.